Pemanfaatan fraksi aktif ekstrak kecambah Vigna radiata L. sebagai bioregulator pada kultur in vitro planlet Nepenthes sp. menggunakan medium Murashige & Skoog - Puspita, Dewi; Santoso, Maya (Lembaga Publikasi Ilmiah Nusantara, 2025)
This study aimed to evaluate the potential of the active fraction from Vigna radiata L. sprout extract as a natural bioregulator in the in vitro culture of Nepenthes sp. plantlets using Murashige & Skoog (MS) medium. The use of natural plant growth regulators offers an alternative to reduce dependence on synthetic growth regulators, particularly for carnivorous plants that generally exhibit slow growth rates and sensitive responses in tissue culture. The active fraction was obtained through stepwise fractionation to isolate bioactive compounds that may stimulate plant growth. Plantlets were cultured on MS medium supplemented with various concentrations of the active fraction to observe growth responses, including shoot elongation, leaf number, root development, and overall biomass accumulation. The results are expected to identify the optimum concentration that provides the highest growth stimulation, demonstrating that Vigna radiata sprout extract can serve as an efficient, economical, and environmentally friendly natural bioregulator. These findings contribute to the development of improved propagation protocols for Nepenthes sp. and highlight the potential of sprout-derived natural compounds for broader applications in plant tissue culture.